Pendampingan Lansia dalam Pelayanan Keperawatan Mandiri Dengan Masalah Nyeri Kronik - Syaifurrahman Hidayat; Mujib Hannan (Jurnal ABDIRAJA, 2022)
The decreasing of biological function in the aging process affecting a damage in organ tissue in the elderly, so they are easy to be susceptible of diseases including chronic pain. Pain management in the elderly with osteoarthritis in the community in large mount use pain relievers, and rarely use non-pharmacological therapy, even though the use of non-pharmacological pain management has a smaller risk of drug side effects. The solution needed to be done is Assistance to elderly in Independent Nursing Services with Chronic Pain Problems. The implementation method is providing health education to elderly families, mentoring chronic pain management independently, assisting in developing an integrated healthcare center program for the elderly on chronic pain management and conducting training for elderly health cadres. The results of the implementation of mentoring for elderly were carried out in four activities including health counseling for the elderly and family, assistancing in managing chronic pain independently, optimizing the elderly integrated healthcare center program on pain management and training for elderly health cadres. Assistancing for the elderly in independent nursing services as part of human resource development efforts in improving the handling of problems that occur in the elderly, one of which is chronic pain in the elderly, namely with independent nursing services that can be done at home, so that it becomes part of promotive and preventive efforts